2022
DOI: 10.3847/1538-4357/ac9475
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Shock During a Nova Outburst: An Origin of Multiple Velocity Systems in Optical Spectra and of High-energy Emissions

Abstract: We propose a theoretical explanation of absorption/emission line systems in classical novae based on a fully self-consistent nova explosion model. We found that a reverse shock is formed far outside the photosphere (≳1013 cm) because later-ejected mass with a faster velocity collides with earlier-ejected matter. Optically thick winds blow continuously at a rate of ∼10−4 M ☉ yr−1 near the optical maximum, but its velocity decreases toward the optical maximum and increases af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 88 publications
(253 reference statements)
3
13
0
Order By: Relevance
“…V5668 Sgr Cheung et al (2016)) gamma (>100 MeV) episodes. Where some have argued for a white dwarf spin correlation to the gamma periodicity (ASASSN-16ma Li et al (2017)), here we posit several forward and reverse shocks in both polar and equatorial nova shell regions to give the observed structured optical and gamma-ray light curve of V906 Car, similar to the theoretical work of Hachisu & Kato (2022), effectively leading to the shaping of the nova shell as observed in its nebular phase. Steinberg & Metzger (2020) discuss varying velocity outflows over the course of a nova eruption leading to flares and complex velocity evolution of absorption and emission components of spectral lines, which is what we propose here being observed in V906 Car.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…V5668 Sgr Cheung et al (2016)) gamma (>100 MeV) episodes. Where some have argued for a white dwarf spin correlation to the gamma periodicity (ASASSN-16ma Li et al (2017)), here we posit several forward and reverse shocks in both polar and equatorial nova shell regions to give the observed structured optical and gamma-ray light curve of V906 Car, similar to the theoretical work of Hachisu & Kato (2022), effectively leading to the shaping of the nova shell as observed in its nebular phase. Steinberg & Metzger (2020) discuss varying velocity outflows over the course of a nova eruption leading to flares and complex velocity evolution of absorption and emission components of spectral lines, which is what we propose here being observed in V906 Car.…”
Section: Discussionsupporting
confidence: 74%
“…Supporting the observations are a series of theoretical works, e.g. Metzger et al (2014); Derdzinski et al (2017); Steinberg & Metzger (2020); Hachisu & Kato (2022). Slow evolving dust producing novae, similar to V906 Car, have a tendency to feature the brightest (V1324 Sco Finzell et al (2018)) and longest duration (e.g.…”
Section: Discussionmentioning
confidence: 73%
“…Such a large variety in wavelengths (or energies) of emissions indicates that various emissions originate from different places or times of the nova ejecta. Hachisu & Kato (2022) and Hachisu & Kato (2023) proposed nova ejecta evolution models based on the fully selfconsistent nova outburst model of Kato et al (2022a). The authors found that a strong shock naturally arises in nova ejecta far outside the WD photosphere without ad hoc or arbitrary settings on the nova ejecta, and elucidated the origin of nova absorption/emission line systems raised by McLaughlin (1942).…”
Section: Shock Formationmentioning
confidence: 99%
“…In the present work, we elucidate the nature of the classical nova V339 Del based on our nova shock model (Hachisu & Kato 2022. The outburst of V339 Del was optically discovered by K. Itagaki at 6.8 mag on UT 2013 August 14.584 (JD 2,456,519.084;Nakano & Samus 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation